The Influence of Ethical Leadership on Financial Performance and Human Resource Satisfaction in Islamic Banking Institutions - Yofy Syarkani (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This literature review explores the influence of ethical leadership on financial performance and human resource satisfaction within Islamic banking institutions. Ethical leadership, grounded in principles of integrity, fairness, and accountability, is increasingly recognized as a critical determinant of organizational outcomes. The review synthesizes findings from peer-reviewed articles published over the past decade, focusing on empirical studies within Islamic financial contexts. Results indicate that ethical leadership positively correlates with improved financial performance, largely through enhanced stakeholder trust, risk mitigation, and reputational strength. Additionally, employee satisfaction appears to be significantly influenced by leaders who demonstrate ethical conduct, transparency, and alignment with Islamic values. The analysis further highlights that ethical leadership in Islamic banking institutions is often reinforced by Sharia principles, creating a unique cultural and normative framework. However, discrepancies in implementation practices and measurement approaches remain notable across institutions and regions. This study identifies theoretical gaps and calls for more integrated models that link ethical leadership with performance metrics and employee well-being in Islamic finance. It also emphasizes the need for cross-cultural and longitudinal studies to capture the dynamic nature of leadership ethics. The review offers strategic implications for policymakers and banking executives seeking to strengthen institutional sustainability and ethical governance.